The economic growth of the ukrainian economy: the role of natural resource potential - Popova, Olga (Видавництво Львівської політехніки, 2013)
Natural resource use gives rise to public and private goods and services in national economy. Decision making in large corporations involved in the extraction and processing of natural resources in Ukraine, based on generation of profit, is the legitimate possibility of transferring responsibility and payment for environmental pollution and depletion of natural resources on the state. And the lack of «fair» money value of natural resources and ecological damage results in excessive production of private welfare with a minimum production of public welfare. As a result disproportions accumulate that endanger a possibility of longterm economic growth.
Keywords: natural resource; potential; economic growth; welfare; model